Application of proton transfer reaction mass spectrometry for the assessment of toluene removal in a nonthermal plasma reactor. (23rd October 2018) - Guo, Teng; Peng, Zhen; Li, Xueshuang; Zhu, Hui; Xu, Li; Dong, Junguo; Feng, Jialiang; Cheng, Ping; Zhou, Zhen
Abstract: Proton transfer reaction mass spectrometry (PTR‐MS) is a mature technique for the real‐time measurement and monitoring of volatile organic compounds in the atmosphere. In this paper, a modified quantification method for PTR‐MS was used to assess the performance of nonthermal plasma (NTP) reactor for the removal of toluene which was widely used in industrial production processes. Toluene and 11 corresponding organic by‐products were tentatively identified and quantified by a proton transfer reaction time‐of‐flight mass spectrometer. The degradation dynamics of toluene and the formation of organic by‐products were monitored in real‐time (resolution = 1 second) under "plasma off" and "plasma on" conditions. We conclude that initial concentration and gas flow rate were the key parameters in the health risk assessment of NTP for the removal of toluene. The toluene removal efficiency and CO2 selectivity decreased with increasing upstream toluene concentration or gas flow rate, whereas the health risk influence index increased with increasing upstream toluene concentration or gas flow rate. The highest removal efficiency of toluene (100%), CO2 selectivity (53.2%), and the best health risk influence index for organic by‐products (0.11) were achieved when the toluene concentration was kept at 105 ppmv and flow rate at 0.4 L/minute. The results demonstrate that PTR‐MS is a promising tool to improve the practical applications of volatile organic compound removal by NTP because it can be used to optimize the NTP working conditions by providing a precise, fast, and clear health risk assessment for organic by‐products based on their real‐time analysis.